2023
DOI: 10.1159/000533237
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Angiodysplasia in Patients with Severe Aortic Stenosis: The Endoscopic Features of Heyde’s Syndrome

Satoshi Sugino,
Ken Inoue,
Kan Zen
et al.

Abstract: <b><i>Introduction:</i></b> Aortic stenosis (AS) is sometimes associated with gastrointestinal bleeding, and this phenomenon is known as Heyde’s syndrome. Such bleeding is most often considered to originate from gastrointestinal angiodysplasias, but the frequency and endoscopic features of such bleeding remain unclear. This study aimed to determine the frequency and endoscopic features of gastrointestinal angiodysplasia in patients with severe AS. <b><i>Patients and Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Another previous study showed that 22.5% of patients with severe AS underwent endoscopic examinations in a clinical setting. Of those, 28.8% had angiodysplasia, 13.4% in upper gastrointestinal endoscopy, 71.4% in enteroscopy, and 26.3% in lower gastrointestinal endoscopy [ 28 ]. In this current study, 27.4% of MR patients underwent endoscopic examination and only 8.7% of patients had angiodysplasia, including 4.8% and 7.7% of patients in the stomach and colon, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Another previous study showed that 22.5% of patients with severe AS underwent endoscopic examinations in a clinical setting. Of those, 28.8% had angiodysplasia, 13.4% in upper gastrointestinal endoscopy, 71.4% in enteroscopy, and 26.3% in lower gastrointestinal endoscopy [ 28 ]. In this current study, 27.4% of MR patients underwent endoscopic examination and only 8.7% of patients had angiodysplasia, including 4.8% and 7.7% of patients in the stomach and colon, respectively.…”
Section: Discussionmentioning
confidence: 99%